Genetics of the hippocampal transcriptome in mouse: a systematic survey and online neurogenomics resource - Rupert W Overall; Gerd Kempermann; Jeremy Peirce; Lu Lu; Dan Goldowitz; Fred H Gage; Shirlean Goodwin; August B Smit; David C Airey; Glenn D Rosen; Leonard C Schalkwyk; Thomas R Sutter; et al. (Frontiers in Neuroscience, 2009)
Differences in gene expression in the CNS influence behavior and disease susceptibility. To systematically explore the role of normal variation in expression on hippocampal structure and function, we generated an online microarray database for a diverse panel of strains of mice, including most common inbred strains and numerous recombinant inbred lines (www.genenetwork.org). Using this resource, coexpression networks for families of genes can be generated rapidly to test causal models related to function. The data set is optimized for quantitative trait locus (QTL) mapping and was used to identify over 5500 QTLs that modulate mRNA levels. We describe a wide variety of analyses and novel synthetic approaches that take advantage of this resource, and demostrate how both the data and associated tools can be applied to the study of gene regulation in the hippocampus and relations to structure and function.